Teachers’ Strategies in Teaching English Vocabulary to Young Learners - Andriani, Agis; Rosmala, Dewi; Nanzila, Intan (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Teaching English vocabulary to secondary school students requires effective strategies to support vocabulary acquisition. However, there is still a lack of a comprehensive understanding of teachers’ most effective techniques. Therefore, this study aims to identify teachers’ strategies for teaching English vocabulary to junior high school students in Tasikmalaya. The research used a descriptive case study design, with data collected through semi-structured interviews with a teacher who is an English education graduate. The data were analyzed using qualitative methods as described by Miles, Huberman, and Saldana (2014). The findings highlight three main areas: (1) Vocabulary learning strategies, such as games, pictures, realia, songs, translation, gestures, and memorization; (2) Classroom management strategies, including fostering enthusiasm, organizing group activities, encouraging participation, and creating a positive learning environment; (3) Vocabulary assessment, utilizing various methods to measure vocabulary proficiency. The study concludes that these strategies foster a positive learning environment and motivate students to expand their English vocabulary. The findings also suggest that enhancing teachers’ creativity in developing these strategies can significantly improve students’ vocabulary acquisition.